Between construction yard and village: Changing relations of caste and hierarchy among Madhya Pradesh's labouring classes - Arnaud Kaba (Journal of Agrarian Change, 2022)
In Madhya Pradesh, India, rural migrant workers hired in flyover's construction yards experiment a space of work where the social practices relating to caste separation and hierarchy are temporally softened. This paper shows that these processes of conviviality, through mixing between castes and trans-communitarian work identities based on the hierarchies of labour, are taking part in the lower classes' long quest for less oppressive labour relations. Starting from the construction yard, and then going to the village, this paper shows that the labour relations involved in the circulation of rural migrants to the flyover construction yards are contributing to shaping their complex and flexible social consciousness in a context of slow reconfiguration of oppressive rural labour relations.
Keywords: 630; caste; classes of labour; conviviality; Indian labour; migration